Supervisi Pendidikan Berbasis Tauhid - Wiji Hidayati; Zakiatus Syarifah; Sedya Santosa (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to identify and describe the supervision of monotheism-based education. This research is a literature study so that the data collection technique is in the form of documents from libraries, both books, journals and so on. The results of this study suggest that supervision can be qualified with the right supervision model in order to be able to bring positive changes to teachers who still need improvement, of course with supervision through supervision carried out and implementation innovations will give positive results. In carrying out supervision of teachers, school principals should use appropriate supervision approaches and techniques, especially approaches by touching the heart of how a servant is obliged to his Lord and then bringing up professional servants at work. Supervision of monotheism-based education is a process of monitoring the improvement of teachers accompanied by the internalization of the values of monotheism. The values of monotheism or Islamic values are applied in all aspects of the assessment. The presence of the monotheism paradigm finds its urgency for the development of learning theory and practice.